2015
DOI: 10.1007/s10916-015-0325-0
|View full text |Cite
|
Sign up to set email alerts
|

StratBAM: A Discrete-Event Simulation Model to Support Strategic Hospital Bed Capacity Decisions

Abstract: The ability to accurately measure and assess current and potential health care system capacities is an issue of local and national significance. Recent joint statements by the Institute of Medicine and the Agency for Healthcare Research and Quality have emphasized the need to apply industrial and systems engineering principles to improving health care quality and patient safety outcomes. To address this need, a decision support tool was developed for planning and budgeting of current and future bed capacity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…DES has proven valid and useful in various healthcare settings to model the impact of patient pathway changes, 8 redesign, 10 and capacity changes. 9 However, the complexity of the service, patient population, and case mix required simplifications and assumptions to be made. These were verified by RDC key team members.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…DES has proven valid and useful in various healthcare settings to model the impact of patient pathway changes, 8 redesign, 10 and capacity changes. 9 However, the complexity of the service, patient population, and case mix required simplifications and assumptions to be made. These were verified by RDC key team members.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…It is important to note that only 12 papers [3,22,52,60,73,93,96,119,120,124,143,170] state that their research/product was implemented/informed policythis is only 6.9% of the papers surveyed. Previous reviews have found similar results in regards to implementation (e.g.…”
Section: Obtaining the Pathwaymentioning
confidence: 99%
“…Scope Hospital [8, 21, 23, 27, 29-31, 36, 41, 51, 64, 67, 74-76, 79, 85, 108, 111, 114-117, 134, 142, 145-148, 152, 158, 160, 165, 166, 170, 177, 178, 184, 190, 202, 203, 209] Department [12,14,15,17,18,46,50,52,57,62,68,100,113,125,129,141,151,153,154,161,163,164,167,169,171,182,185,187,212] Clinical [1, 3, 5, 10, 11, 13, 16, 19, 20, 22, 32-35, 40, 42, 43, 45, 47, 53, 60, 70-73, 80-83, 87-99, 102, 107, 110, 112, 121, 124, 126-128, 133, 136, 139, 140, 149, 162, 179, 183, 186, 188, 191, 192, 195, 197-201, 204-206, 210, 211] Disease [4, 7, 9, 13, 24, 25, 37, 39, 43, 48, 49, 54-56, 58, 66, 86, 101-104, 118-120, 122, 128, 131, 138, 143, 144, 150, 157, 172, 196, 211] Table A5…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used in studies in the field of hospital management, health resource planning, and to improve patient flow and waiting time at hospitals. [15][16][17][18][19][20][21] However, relatively few studies have focused on pharmacy systems. [22][23][24] In the present study, we aimed to clarify the impact of ODP on patient waiting time by conducting a survey at a dispensing pharmacy, and propose an improvement strategy with use of DES model.…”
mentioning
confidence: 99%